Dialogues on Development. On Dependency - Souza, Angelita Matos (Boletim Campineiro de Geografia, 2018)
Resenha do livro: Ushehwedu Kufakurinani; Ingrid Harvold Kvangraven; Frutuoso Santana; Maria Dyveke Styve (editors). Dialogues on Development. On Dependency